2016
DOI: 10.1002/chem.201604809
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Tuning of an Anionic CoII‐MOF through Deionization of the Framework: Spin‐Canting, Spin‐Flop, and Easy‐Plane Magnetic Anisotropy

Abstract: An anionic Co -MOF, (Me NH )[Co (Me NH) (OH)(SDBA) ] (1) (H SDBA=4,4'-sulfonyldibenzoic acid) consisting of highly symmetric Co (μ -OH) triangles exhibits spin-canting, spin-flop, and easy-plane magnetic anisotropy. Measurement on a single crystal shows that the ab plane of 1 is the easy magnetization plane. After structural modification through simultaneous removal of the coordinated dimethylamine (DMA) molecule at the Co center and the ionic groups DMA and OH , the resulting neutral amorphous framework 2 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…First of all, although our definition of spin triangles in theory encompasses Co II (S = 3/2) ions, practically only ah andfulo f Co II spin triangles have been reported to date. [55][56][57][58][59][60][61][62][63][64] Only in a couple of cases were magnetic data quantitatively analyzed, undoubtedly owing to the complications arising from the strongspin-orbit coupling (SOC) of Co II in near-octahedralenvironments. [64,65] EPR or single-crystal magnetic studies are yet to be reported.…”
Section: Variations On At Hemementioning
confidence: 99%
“…First of all, although our definition of spin triangles in theory encompasses Co II (S = 3/2) ions, practically only ah andfulo f Co II spin triangles have been reported to date. [55][56][57][58][59][60][61][62][63][64] Only in a couple of cases were magnetic data quantitatively analyzed, undoubtedly owing to the complications arising from the strongspin-orbit coupling (SOC) of Co II in near-octahedralenvironments. [64,65] EPR or single-crystal magnetic studies are yet to be reported.…”
Section: Variations On At Hemementioning
confidence: 99%
“…6–8 The magnetic properties of CPs are diverse and closely related to the ligand field and magnetic exchange pathways between the neighboring spins, which are susceptible to their chemical components and structural features. 9–12 A deep view of magneto-structural correlations for CPs is very important, which may result in a better understanding and discovery of fundamental and new magnetic phenomena in molecular materials and direct the assembly of molecular magnets with specific properties. 13,14 The CPs with a low dimensional topology or isolated polynuclear cluster units can help to better understand the magneto-structural correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, exploring MOFs containing tetrahedral coordination of the first-row transition metal centers with high-spin electron configurations to realize the high catalytic activity has become a hot spot. There are two common methods of achieving tetrahedral coordination for metal centers: (1) Creating tetrahedral coordination metal centers through coordinated solvent removal . It is the most widely exploited method by removing metal-bound solvent molecules (DMF, H 2 O, MeOH, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…There are two common methods of achieving tetrahedral coordination for metal centers: (1) Creating tetrahedral coordination metal centers through coordinated solvent removal. 15 It is the most widely exploited method by removing metal-bound solvent molecules (DMF, H 2 O, MeOH, etc.) in MOFs, which frequently results in the collapse of the structure or transformation of the metal coordination geometry.…”
Section: Introductionmentioning
confidence: 99%